(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The law dealing with life sciences (biolaw) should be characterised by being up-to-date, open to scientific evidence and ethical pluralism and attentive to the particularities of different concrete cases. The article considers the most recent Italian constitutional case-law on end-of-life decisions (ord. 207/2018 and decision 242/2019) in the light of these features, noting many pros and a few cons.